STRATEGI DAN ARAH KEBIJAKAN BISNIS PERBANKAN NASIONAL - Teddy Hikmat Fauzi (Jurnal Keuangan dan Perbankan, 2010)
Characteristics of external and internal environment significantly influenced the implementation of strategiesand could explain their relation with environmental factors and strategic management process. Rightlybank management to make observations and to consider seriously and carefully all developments happenedin the outside environment, particularly those identified as factors which would affect company operations.Another fundamental reason that required the attention of the bank focused on the importance of thesefactors. When the external strategic management process carried out, according to the results of theresearch, the characteristic of the external environment did not show a direct influence significantly on theeffectiveness of bank business, but gave the positive influence through formulation and implementation ofthe strategy done well. It could be indicated that BNI bank units in 04 west java region and state banks ingeneral still needed observations on internal factors but in order to achieve bank objectives (effectiveness).Then these factors needed to be adjusted with the opportunities. Threats originating from the externalenvironment were also strategic options that would be taken.